2018
DOI: 10.31710/pjp/0051.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Career and Talent Development Self-Efficacy of Filipino Students: The Role of Self-Compassion and Hope

Abstract: Recent reforms in the Philippine educational system (i.e., Enhanced Basic Education Act of 2013, the implementation of the K to 12 Program) aim to prepare students for lifelong learning, enhance The recent reforms in the Philippine educational system aim to develop lifelong learners who are competent in their chosen career and capable of contributing to society. Career and talent development self-efficacy is an enabling resource that could facilitate the realization of these goals. The present study examines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…Turan (2013, 2017) found that career and talent development self-efficacy had positive relationships with perceived social support from friends, meta-cognitive awareness, satisfaction with life, career adaptability, and coping with career indecision. Also, Nalipay and Alfonso (2018) found positive relationships between career and talent development self-efficacy and hope. There are few studies examining career and talent development self-efficacy; thus, examining studies on career decision-making self-efficacy can contribute to a better understanding of the theoretical framework in the present study.…”
Section: Career and Talent Development Self-efficacymentioning
confidence: 88%
See 1 more Smart Citation
“…Turan (2013, 2017) found that career and talent development self-efficacy had positive relationships with perceived social support from friends, meta-cognitive awareness, satisfaction with life, career adaptability, and coping with career indecision. Also, Nalipay and Alfonso (2018) found positive relationships between career and talent development self-efficacy and hope. There are few studies examining career and talent development self-efficacy; thus, examining studies on career decision-making self-efficacy can contribute to a better understanding of the theoretical framework in the present study.…”
Section: Career and Talent Development Self-efficacymentioning
confidence: 88%
“…The concept of career and talent development self-efficacy refers to the belief that the person has the capacity to develop skills required for their desired career (Buenconsejo and Datua, 2020), with high levels helping students to strengthen and optimize their skills and capabilities (Buenconsejo and Datua, 2020; Nalipay and Alfonso, 2018). In particular, it refers to the belief that students will develop the required talents and skills to work in a certain career field (Yuen et al., 2010).…”
Section: Career and Talent Development Self-efficacymentioning
confidence: 99%
“…Self-efficacy is shown to be positively related to the positive components of self-compassion and is negatively predicted by over-identification [37,38]. In addition to the hopelessness of future and career prospects suffered by students today, career and talent development self-efficacy was shown to be positively correlated with self-compassion [39].…”
Section: Self-compassion and Self-schemamentioning
confidence: 88%
“…An employee's ability influences his performance and motivation level (Beattie, Woodman, Fakehy, & Dempsey, 2016). Traits like self-compassion (Nalipay & Alfonso, 2018) and dimensions of determination have connected to expanding career exploration and development of employees' talent in an organization (Datu, Yuen, & Chen, 2017). Employees seldom carry out the task when the output seems to be abortive.…”
Section: Introductionmentioning
confidence: 99%